2022
DOI: 10.13189/ujph.2022.100609
|View full text |Cite
|
Sign up to set email alerts
|

Can a Healthy Lifestyle Reduce Feelings of Anxiety during the COVID-19 Pandemic?

Abstract: The implemented outdoor activity restrictions throughout the COVID-19 pandemic have caused a change in people's lifestyles. The significant changes that can be seen are the reduced number of people's participation in physical activities and the change in their dietary patterns [1]. This condition also affects the anxiety of everyone. A lifestyle related survey was conducted on 274 students at the University of Education Indonesia using the Fantastic Instrument developed by Dr. Douglas Wilson from the Departmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Riise, Moen, and Nortvedt (2003) found that physical activity was positively correlated with the physical dimension of quality of life, providing a better understanding of how different activity patterns influence the health, well-being, and quality of life of adolescents, thereby contributing to the development of adolescent activity (Dumuid et al, 2017). Former athletes show greater resilience and a better quality of life in emotional aspects compared to non-athletes (Cevada et al, 2012), as well as having lower levels of stress (Gumilar et al, 2022;Nuryadi et al, 2019). Lifestyle conditions through the parameters measured are the condition of family and friends, physical activity, nutrition or nutritional intake, cigarette consumption, alcohol consumption, sleep quality and stress levels, personality, ability to understand events, and satisfaction with a career (Komariyah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Riise, Moen, and Nortvedt (2003) found that physical activity was positively correlated with the physical dimension of quality of life, providing a better understanding of how different activity patterns influence the health, well-being, and quality of life of adolescents, thereby contributing to the development of adolescent activity (Dumuid et al, 2017). Former athletes show greater resilience and a better quality of life in emotional aspects compared to non-athletes (Cevada et al, 2012), as well as having lower levels of stress (Gumilar et al, 2022;Nuryadi et al, 2019). Lifestyle conditions through the parameters measured are the condition of family and friends, physical activity, nutrition or nutritional intake, cigarette consumption, alcohol consumption, sleep quality and stress levels, personality, ability to understand events, and satisfaction with a career (Komariyah et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Herein lies an opportunity to unravel how intrinsic motivation influences the engagement of university students with softball, offering insights into the factors propelling skill refinement and shaping the holistic sporting experience of these students (Baena-Extremera et al, 2014;Buning, 2016;Ryan & Deci, 2020). Additionally, it is noteworthy that individuals who have embraced a physically active lifestyle may be particularly susceptible to experiencing the profound influence of less feelings of anxiety (Gumilar et al, 2022). It can enhance intrinsic motivation, as their ongoing engagement in physical activities can further reinforce the intrinsic rewards and satisfaction derived from participation in sports like softball (Kim et al, 2022;Pelletier et al, 1995;van Wersch, 2005).…”
Section: Introductionmentioning
confidence: 99%